The miR-133b/brefeldin A-inhibited guanine nucleotide-exchange protein 1 (ARFGEF1) axis represses proliferation, invasion, and migration in cervical cancer cells. Issue 2 (1st February 2022) - Jiang, Lingling; Wang, Xuexin
ABSTRACT: Cervical cancer is a common gynecological malignancy, and miR-133b is an abnormally expressed cervical cancer gene, which suggests that miR-133b may be involved in the occurrence and development of cervical cancer. However, the underlying mechanism is still unclear. miR-133b was overexpressed or silenced in the cervical cancer cell line C33A. Brefeldin A-inhibited guanine nucleotide-exchange protein 1 (ARFGEF1) was combined with overexpression of miR-133b in C33A cells. Cell Counting Kit-8, clone formation, and Transwell assays were performed to determine the influence of miR-133b and ARFGEF1 on clone formation, proliferation, migration, and invasion of C33A cells. The interaction between miR-133b and ARFGEF1 was verified using a luciferase reporter assay. Finally, the mRNA and protein expression of miR-133b and ARFGEF1 in the tumor and adjacent normal tissues of cervical cancer patients was detected by real-time quantitative PCR, Western blotting, and immunohistochemistry. The results indicated that miR-133b up-regulation suppressed the proliferation, invasion, migration, and clone formation abilities of C33A cells ( P < 0.05). However, silence of miR-133b promoted the proliferation, invasion, and migration of C33A cells ( P < 0.05). Clone formation ability of C33A cells was also elevated by miR-133b deficiency ( P < 0.05). Moreover, miR-133b interacted with ARFGEF1 and repressed ARFGEF1 expression in C33A cells ( P < 0.05). ARFGEF1 overexpression weakened miR-133b overexpression-mediated inhibition of proliferation, invasion, and migration of C33A cells ( P < 0.05). miR-133b expression was decreased, and ARFGEF1 was up-regulated in tumor tissues of cervical cancer patients ( P < 0.05). All results revealed that miR-133b suppresses cervical cancer progression by inhibiting proliferation, invasion, and migration of cervical cancer cells via targeting ARFGEF1. Thus, our study determined the mechanism of miR-133b in cervical cancer, and confirmed miR-133b/ARFGEF1 may become a potential therapeutic target for cervical cancer.